Development of Hot Air Dryer Conveyor for Automotive Tampo Printing Parts - Ali Rospawan; Joni Welman Simatupang; Irwan Purnama (Green Intelligent Systems and Applications, 2022)
This paper presents the development of a hot air dryer conveyor for the automotive industry in the tampo printing part process. The research started by designing and creating the actual device that is ready to use and be implemented in the industry. The method provides the detail of the drying chamber, hot air dryer, and its mathematical model. The chosen hot air dryer is Suiden SHD-9F II and is operated on the factory default setting of auto-tuning mode. The performance evaluation studies the indicator performance of hot air dryer for the chosen size of drying chamber, the robustness of the system against fluctuating environmental air change rate, the ducting capacity, and the damper opening value estimation performance. The result of this system is working well at specification requirement of air change rate from 15 to 21 at 80% of its maximum capacity for error compensation and its already being successfully implemented.